2017
DOI: 10.12737/stp-34201703
|View full text |Cite
|
Sign up to set email alerts
|

North-south asymmetry of ultra-low-frequency oscillations of Earth’s electromagnetic field

Abstract: Abstract. In the paper, we present the result of an experimental study of north-south asymmetry of ultralowfrequency electromagnetic oscillations IPCL. This study is based on observations made at Mirny Observatory (Antarctica). IPCLs are excited in the dayside sector of the auroral oval in the range 3-10 min periods and represent one of the most powerful types of oscillations of Earth's magnetosphere. These oscillations were discovered in the 1970s during IPhE AS USSR polar expeditions organized by Prof. V.A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Besides, as has been shown previously [Guglielmi et al, 2019], the DS occurrence rate also depends on the vertical inclination of the IMF vector (but not on the sign of B z ) determining the foreshock orientation. Thus, there is reason to assume that the signals are generated in a foreshock or even ahead of it in SW, and with a favorable relative position of the IMF vector, the magnetic field line passing through the observation station, and the magnetic dipole tilt they penetrate into Earth's surface.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Besides, as has been shown previously [Guglielmi et al, 2019], the DS occurrence rate also depends on the vertical inclination of the IMF vector (but not on the sign of B z ) determining the foreshock orientation. Thus, there is reason to assume that the signals are generated in a foreshock or even ahead of it in SW, and with a favorable relative position of the IMF vector, the magnetic field line passing through the observation station, and the magnetic dipole tilt they penetrate into Earth's surface.…”
Section: Discussionsupporting
confidence: 54%
“…We have already examined DS that occur in the polar areas in [Guglielmi et al, 2019]. In that paper, we have found that the signal occurrence rate depends on the orientation of the interplanetary magnetic field (IMF) in the XOZ plane.…”
Section: Discrete Frequency-dispersed Signalsmentioning
confidence: 99%
See 3 more Smart Citations